2017
DOI: 10.5056/jnm17017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cognitive Behavior Therapy on Heart Rate Variability in Young Females with Constipation-predominant Irritable Bowel Syndrome: A Parallel-group Trial

Abstract: Background/AimsThe relation between heart rate variability (HRV) as non-invasive biomarkers of autonomic function and cognitive behavior therapy (CBT) as non-pharmacological treatments has rarely been examined in patients with constipation-predominant irritable bowel syndrome (IBS-C). The purpose of this study is to evaluate the efficacy of an 8-week CBT intervention on HRV and IBS symptoms, and the correlation of changes in HRV with changes in IBS symptoms among young female nursing students with IBS-C. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 52 publications
1
19
0
1
Order By: Relevance
“…Here's the good news: these phenomena are reversible! In line with research in adults (Chambers & Allen, 2002; Jang, Hwang, Padhye, & Meininger, 2017), we have previously shown, that HRV re‐increases following antidepressant treatment with selective serotonin reuptake inhibitors in adolescents with depression (Koenig et al, 2018). Clinical improvement (decrease in depression severity) was associated with increased HRV and decreased HR.…”
Section: A Dynamical Model Of Neurovisceral Integrationsupporting
confidence: 88%
“…Here's the good news: these phenomena are reversible! In line with research in adults (Chambers & Allen, 2002; Jang, Hwang, Padhye, & Meininger, 2017), we have previously shown, that HRV re‐increases following antidepressant treatment with selective serotonin reuptake inhibitors in adolescents with depression (Koenig et al, 2018). Clinical improvement (decrease in depression severity) was associated with increased HRV and decreased HR.…”
Section: A Dynamical Model Of Neurovisceral Integrationsupporting
confidence: 88%
“…Reduced cardiovagal modulation occurs in chronic pelvic pain, complex regional pain syndrome, fibromyalgia, chronic neck pain, and other chronic pain syndromes and may predispose to or result from chronic pain. A prospective study in adults with IBS showed increased cardiovagal modulation as subjects improved while undergoing cognitive behavioral therapy (CBT) . Since CBT itself is known to increase cardiovagal modulation, this result could reflect either CBT or disease improvement or both.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study in adults with IBS showed increased cardiovagal modulation as subjects improved while undergoing cognitive behavioral therapy (CBT). 22 Since CBT itself is known to increase cardiovagal modulation, this result could reflect either CBT or disease improvement or both. Our long-term goal is to distinguish these possibilities by following our cohort prospectively as they improve irrespective of treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…CBT is based on reversing maladaptive thoughts, behaviors, and emotions that result from ongoing hypervigilance, thereby affecting the altered gut sensation and changing behaviors (Levy et al, ). As proof of concept, a study showed significant increase in high frequency HRV with concurrent decrease in GI symptoms, anxiety and stress in constipation‐predominant IBS after 8 weeks of CBT (Jang, Hwang, Padhye, & Meininger, ).…”
Section: An Autonomic State Regulation Perspective On Treatment and Pmentioning
confidence: 99%
“…An autonomic threat response can be facilitated by ventral vagal complex (VVC) withdrawal, sympathetic activation, dorsal vagal complex activation, or their combination. Prolonged threat activation disrupts psychosocial and gastrointestinal function and may be maintained by impaired brain-body feedback loops, threat cue sensitization, disruption of affiliative social interactions that stimulate safety-related systems, and adverse niche construction in high frequency HRV with concurrent decrease in GI symptoms, anxiety and stress in constipation-predominant IBS after 8 weeks of CBT (Jang, Hwang, Padhye, & Meininger, 2017).…”
Section: Cognitive Behavioral Therapymentioning
confidence: 99%